Rozvoj marketingových aktivit posilujících konkurenceschopnost firmy - Kaufmanová, Marie (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Úkolem diplomové práce bylo zhodnotit současnou situaci společnosti Liberecká IS, a. s. pomocí strategické analýzy, a na základě jejích výsledků navrhnout marketingové aktivity a jejich rozvoj, které by podporovaly konkurenceschopnost společnosti na trhu. V rámci těchto marketingových aktivit byl proveden marketingový průzkum největšího zákazníka společnosti, který potvrdil a v některých případech vyvrátil tušení společnosti ohledně kvality služeb, které jsou poskytovány a spokojenosti zákazníků společnosti. Průzkum tak nastínil další činnosti, které povedou ke zvyšování spokojenosti zákazníků a tím i větší konkurenceschopnosti společnosti.

The aim of this master’s thesis is to evaluate the contemporary position of company Liberecká IS and, with the help of strategic analyses and on the base of its results, to propose marketing activities and their development which would support competitive advantage of the company in the market. Within the frame of these marketing activities a marketing research of the largest client of this company was done, which confirmed and in some cases disproved the notion the company had about the quality of services provided and about satisfaction of their clients. In that way the research foreshadowed the next activities that will help to increase client satisfaction and to improve competitive advantage of the company.
Development of Marketing Activities Improving Competitiveness of Company
Keywords: marketing; marketingový výzkum; konkurence; konkurenceschopnost; strategická analýza; outsourcing IS/IT; marketing; marketing research; competition; competitive advantage; strategic analysis